(untitled) (NAU Journal of Technology and Vocational Education, 2026)
This study investigated vocational education and skills acquisition for green jobs and the implications of vocational education and green skills acquisition for climate change adaptation and the Sustainable Development Goals in Adamawa State, Nigeria. A quantitative descriptive survey research design was adopted. The population comprised 1,200 graduates of Technical and Vocational Education and Training institutions in Adamawa State. The sample size for the study was 300 using Krejcie and Morgan (1970) table for sample size. A stratified random sampling technique was employed to ensure representativeness across the different categories of vocational education graduates in Adamawa State. Data were collected using a structured questionnaire titled Vocational Education and Green Skills Questionnaire ‘VEGSQ’. Data were analysed using simple linear regression at .05 level of significance. The results revealed that curriculum relevance significantly influenced adaptive capacity (R = .624, R² = .412, Adj. R2 = .410, t = 14.47, F-value = .0002, p < 0.05); training infrastructure significantly influenced community resilience (R = .598, R² = .357, Adj. R2 = .355, t = 12.89, F-value = .0001, p < .05); technical green skills significantly influenced environmental sustainability (R = 0.671, R² = .450, Adj. R2 = .448, t = 15.62, F-value = .0001, p < .05); and entrepreneurial skills significantly influenced economic empowerment (R = .615, R² = .378, Adj. R2 = .376, t = 13.54, F-value = .0003, p < .05). The study concluded that vocational education and green skills acquisition are significant predictors of climate change adaptation and sustainable development outcomes.